Trilhas da leitura: uma perspectiva de interação família/escola em tempos de pandemia. - Silva, Maria das Dores Soares da (2021)
This dissertation aims to analyze the process of family/school interaction with regard to encouraging the reading of children's books, through a field research, carried out from reading activities proposed in the project "My book, my joy!”, implemented at CEI Jornalista Demócrito Dummar, aimed at children in Infantil III. The proposed research consists of investigating the involvement of families in encouraging reading in online activities proposed in the time of a pandemic. Therefore, we carried out a literature review on the theme that involves children's literature and the reflexes in the formation of future readers. We understand that storytelling practices help in the child's cognitive and social development, expanding, above all, their knowledge of the world. The content of the stories read to children throughout the project, as they deal with social themes, contribute to the formation of the children's personality. In addition, reading, as we know, brings children closer to the process of acquiring writing. The fact that the children remain in their homes, without any face-to-face contact with the school, in the field of the project application methodology, it was decided to develop the activities in their own homes with the help of their guardians. Therefore, the family members were responsible for reading the books, telling and retelling the stories for the children in their homes. With this, it was hoped to increase the involvement of parents in the sense that they would broaden their understanding of the social function of reading and writing in their lives. The research results pointed to situations that can be considered positive, given that there was active participation of families, after the stories and proposed activities, the children expressed themselves, interacted, demonstrating how pleasant it was to hear family stories. The records and impressions obtained and systematized in the data collection showed us its reach as a means of integrating the family into the school context, strengthening ties between school and guardians, at the same time that it served to promote significant learning for children.